2019
DOI: 10.14710/nmjn.v8i2.19111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Yoga Relaxation on Anxiety Levels among Pregnant Women

Abstract: Background: Self-reported maternal mood symptoms during pregnancy have been related to poor birth outcomes, including low birth weight, increased risk of premature delivery, and preeclampsia in the mother. A non-pharmacology method is needed to overcome mood symptoms such as anxiety during pregnancy.Purpose: This research aimed to evaluate the effect of yoga relaxation on anxiety levels among pregnant women at third trimester.Methods: A quasy experimental design has been conducted with using 30 pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
0
20
0
9
Order By: Relevance
“…In this study, the mean age of pregnant women with (15) as unemployed, respectively. Regarding the education of pregnant women, 43.5% (137 people) had the high school diploma or below, 50.2% (158 people) had a bachelor's degree and 6.3% (20 people) had a master's degree or higher.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, the mean age of pregnant women with (15) as unemployed, respectively. Regarding the education of pregnant women, 43.5% (137 people) had the high school diploma or below, 50.2% (158 people) had a bachelor's degree and 6.3% (20 people) had a master's degree or higher.…”
Section: Resultsmentioning
confidence: 95%
“…For many women, pregnancy is a stressful period (14). Experimental studies show that 15-25% of women experience stress, anxiety or depression during pregnancy, which is higher than in the postpartum period (15). The World Health Organization has reported that mental disorders in pregnant women affect fetal and neonatal health (16).…”
Section: Introductionmentioning
confidence: 99%
“…Ellahe et al (2020) found that anxiety levels was lower in yoga group than that in control group (P = 0.003). Yoga had an effect on reducing anxiety levels among pregnant women at the third trimester [34].While most studies have shown that yoga to be useful for depression, one study found both of yoga group and control group reduced the severity of symptoms of depression and anxiety, but they found no evidence of greater decline in depression and anxiety either in yoga group or control group [22]. In a word, the negative psychological effects of depression, stress and anxiety during or after pregnancy will be reduced by yoga intervention.…”
Section: Effect Of Yoga On Psychological Well-beingmentioning
confidence: 99%
“…In this study, 14 trials published between 2015 and 2020 were selected for final analysis. Four studies were originated from the United States [21] [22] [23] [24], three from Japan [25] [26] [27], one each from India [28], Taiwan [29], UK [30], Turkey [31], Iran [32] [33], and Indonesia [34]. As shown in Table 1, the characteristics of the included studies were summarized.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
“…18 Penelitian Novelia tahun 2018 juga menyatakan bahwa Yoga Suryanamaskar dapat menurunkan kecemasan karena adanya peningkatan kemampuan adaptasi respon otonom terhadap stres. 19 Penelitian lain juga menyebutkan bahwa komponen pernapasan pada latihan Yoga Suryanamaskar memiliki efek menenangkan pikiran dan sistem saraf. 20 Hal ini disebabkan karena latihan pernapasan pada yoga mampu memberikan keseimbangan kinerja saraf simpatis dan parasimpatis yang dapat merangsang stimulasi pengeluaran hormon endorfin yang pada umumnya diproduksi di dalam tubuh ketika tubuh merasa nyaman.…”
Section: Pembahasanunclassified